APPLICATION OF MANAGEMENT INFORMATION SYSTEMS IN DISORDER CASES SOULS IN HOSPITAL - Roby Nurbahri (Mount Hope Economic Global Journal, 2024)
The purpose of the research is to find out the application of management information systems to psychiatric disorders in hospitals. This research carries out descriptive research with a qualitative approach. The results of SIMRS research help improve the operational efficiency of hospitals in the field of healthcare. It enables integration of medical and laboratory data, assistance in medical decision-making, and reporting and analysis of hospital performance. However,ining data security and patient privacy during SIMRS use is crucial. There's been progress in psychiatry since civilization.